2023
DOI: 10.1021/acs.joc.3c00408
|View full text |Cite
|
Sign up to set email alerts
|

CuF2/MeOH-Catalyzed N3-Selective Chan-Lam Coupling of Hydantoins: Method and Mechanistic Insight

Abstract: An efficient and practical N-arylation of hydantoins with substituted aryl/heteroaryl boronic acids has been established, assisted by CuF 2 /MeOH under the base and ligand-free conditions at room temperature and open air. The protocol is general, and various N-arylated hydantoins have been prepared in excellent yields with exclusive regioselectivity. The CuF 2 /MeOH combination was explored further to furnish selective N 3 -arylation of 5fluorouracil nucleosides. The efficiency of the protocol was also demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…In parallel, the same research team introduced regioselective ligands and base-free Chan–Lam coupling in hydantoins and 5-fluorouracil nucleosides. 45 Firstly, they analysed the N 3 -selective C–N coupling by reacting hydantoins with aryl/heteroarylboronic acids in the presence of 10 mol% CuF 2 in MeOH at room temperature for 4–20 h (Scheme 37). After that, they established the N 3 -selective coupling in 5-fluorouracil nucleosides under the same conditions for 3–12 h (Scheme 38).…”
Section: Classificationmentioning
confidence: 99%
“…In parallel, the same research team introduced regioselective ligands and base-free Chan–Lam coupling in hydantoins and 5-fluorouracil nucleosides. 45 Firstly, they analysed the N 3 -selective C–N coupling by reacting hydantoins with aryl/heteroarylboronic acids in the presence of 10 mol% CuF 2 in MeOH at room temperature for 4–20 h (Scheme 37). After that, they established the N 3 -selective coupling in 5-fluorouracil nucleosides under the same conditions for 3–12 h (Scheme 38).…”
Section: Classificationmentioning
confidence: 99%
“…Recently, we reported two such coupling processes where the active involvement of base and solvent were discussed in the reaction pathway . In the case of CuOAc 2 /DBU-catalyzed N -arylation of 7-azaindole ( 1 ), a dimeric Cu­(II)-7-azaindole complex has been isolated, which in the presence of base (DBU) provides the active catalytic species, Cu­(II)-7-azaindole-DBU complex to facilitate the cross-coupling reaction (Scheme a) .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Notably, they have the highest number of nitrogen atoms among the stable N-heterocycles and have been widely considered as a suitable precursor to various important scaffolds. [6][7][8][9][10] Recent studies have shown that there has been renewed interest in the preparation of tetrazoles as a substantial number of active pharmaceutical ingredients (API) contain the tetrazole ring. [11][12][13][14] For instance,numerous pharmacological applications of tetrazoles are anti-inflammatory, antihypertensive, anticancer, antiallergic, antibiotic, diuretics and receptor modulatory agents.…”
Section: Introductionmentioning
confidence: 99%
“…Several coordinating ligands, such as N,N'-dimethylethylenediamine (DMEDA)and N,N,N',N'-tetramethylethylenediamine (TMEDA), [33] pyridine N-oxide, [34] thiophene-2carboxylate (TC), [35] 1,10-phenanthroline (phen) [36] and 4-(Dimethylamino)pyridine (DMAP), [37][38][39] have been found promoting various copper catalysed CÀ N bond forming [40][41][42] reactions. These ligands help in preventing copper aggregation, enhancing solubility, stimulate milder conditions and stabilise active catalyst species during the catalysis process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation